PEMBERDAYAAN PERPUSTAKAAN NAGARI UNTUK MENINGKATKAN KEMAMPUAN LITERASI MASYARAKAT DI NAGARI PAKAN SINAYAN KEC. BANUHAMPU KAB. AGAM - Marlini Marlini; Emidar Emidar; Gustina Erlianti; Elva Rahmah (Universitas Negeri Padang, 2021)
This community service or Pengabdian Kepada Masyarakat (PKM) is motivated by the not yet optimal utilization and understanding of the community in managing the village library and the reading habit of most of the community has not grown well. This community service activity was carried out in Nagari Pakan Sinayan, Kec. Banuhampu Kab. Agam. The target of this activity is the village library manager, village mayor, and village community focused on developing community literacy through community activities that are expected to be able to use the library and be able to determine the right source of information. This activity will be held in August – November 2021. The methods used are lectures, hands-on practice, and mentoring. The results showed that the participants were enthusiastic about the activities carried out by the PKM team. Participants can understand and are committed to following up on this PKM activity by empowering the role of the library as a source of information through reading corners that will be developed in each